(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Food arrangement is not only a matter of taste but also of visual appeal, where aesthetics play a crucial role in how meals are perceived and enjoyed. Across cultures and cuisines, chefs and food stylists have long intuitively applied design principles that align closely with mathematical concepts, particularly the Fibonacci sequence and the Golden Ratio. These patterns, found abundantly in nature—from the spiral of a sunflower to the branching of herbs—are often mirrored in culinary presentations to create visually pleasing compositions. This paper explores how these mathematical ideas can be applied to the art of food arrangement, demonstrating that even the structure of a plate can reflect the harmony and order inherent in mathematical beauty.